A corundum reference material for oxygen isotope analysis by secondary ionization mass spectrometry - Schmidt, Sebastian; Schmitt, Axel Karl; Cionoiu, Katharina; McKeegan, Kevin D.; Bindeman, Ilya; Rocco, Tommaso Di; Pack, Andreas (Journal of analytical atomic spectrometry, 2024)
A synthetic laser ruby crystal (HD-LR1) is introduced as a new matrix-matched reference material for secondary ionization mass spectrometry (SIMS) analysis of oxygen isotopes in corundum. Laser fluorination isotope ratio mass spectrometry (LF-IRMS) bulk analyses of multiple mg-sized fragments are homogenous, averaging δ18O = +18.40 ± 0.14‰ (95% confidence interval, n = 23) and Δ′17O = −0.368 ± 0.005‰ (as deviation from slope 0.528 for δ′17O vs. δ′18O at 95% conf., n = 11) relative to Vienna Standard Mean Ocean Water (V-SMOW). SIMS spot analyses show homogeneous O-isotopic values at the ng-scale independent of the location in the HD-LR1 single crystal and in four different crystallographic orientations. However, sample surface topography as an artefact of polishing corundum embedded in epoxy creates excess variability in δ18O within ∼100 μm from the edges of the grains. HD-LR1 is a chemical pure crystal with only Cr as a trace component detected at 276 μg g−1 by EPMA, whereas Be, often introduced in artificial gem enhancement, is <0.002 μg g−1 based on SIMS analyses. Therefore, HD-LR1 can also be used as a reference material for Cr, or as a blank for other trace element analyses of corundum by SIMS or LA-ICP-MS.